Control of cell polarity and mitotic spindle positioning in animal cells. - Ahringer, J. (Current Opinion in Cell Biology, 2003)
Cell polarity is an essential feature of many animal cells. It is critical for epithelial formation and function, for correct partitioning of fate-determining molecules, and for individual cells to chemotax or grow in a defined direction. For some of these processes, the position and orientation of the mitotic spindle must be coupled to cell polarity for correct positioning of daughter cells and inheritance of localised molecules. Recent work in several different systems has led to the realisation that similar mechanisms dictate the establishment of polarity and subsequent spindle positioning in many animal cells. Microtubules and conserved PAR proteins are essential mediators of cell polarity, and mitotic spindle positioning depends on heterotrimeric G protein signalling and the microtubule motor protein dynein.